Development of Intermediate Accounting Teaching Materials: Financial Accounting and Accounting Standards - Nicholas Renaldo; Suhardjo; Suharti; Suyono; Tandy Sevendy (First Ciera Publisher, 2023)
This study aims to develop effective teaching materials for teaching intermediated accounting, with a focus on financial accounting and accounting standards. Good and thoroughly structured teaching materials are very important in preparing students to understand and apply complex concepts in financial accounting and follow relevant accounting standards. This research method is a study of literature, analysis of learning needs, development of teaching materials, and evaluation of the effectiveness of teaching materials developed. A literature study will be conducted to gather information about the latest developments in the field of financial accounting and accounting standards, as well as to study existing teaching materials. The results of making teaching materials show the importance of accounting standards in ensuring the accuracy, relevance, and reliability of financial statements. These standards play an important role in ensuring that financial reports comply with legal obligations and instilling trust among investors and other stakeholders involved in the decision-making process.